Design of a 120V, 5A SEPIC DC-DC Converter for Unipolar 120V DC Microgrid - Obais, Abdulkareem Mokif; Mukheef, Ali Abdulkareem (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2025)
SEPIC is a DC-DC converter that functions in both boost and buck modes, reducing voltage stress on active power switches. It is utilized in electric vehicles, marine vessels, and aircraft to minimize dimensions, mass, maintenance, and operational expenses while enhancing efficiency, safety, and dependability. DC microgrids, characterized by their straightforward topology and economical materials, provide enhanced efficiency relative to AC microgrids. The previous literatures concerning SEPIC converters and DC-DC microgrid’s applications are reviewed in this work. This paper presents a SEPIC-based DC-DC converter designed for direct connection to a unipolar 120V DC microgrid and capable of delivering 600W of DC power. It is outfitted with a current sensor and a protective switch to provide self-protection against microgrid disturbances, such as brief short circuits. The converter has been designed and evaluated using PSpice. The simulation results confirmed the design methods of the proposed converter and demonstrated effective protection against high current events.